Comparison of efficacy and safety between Tacrolimus and Hydrocortisone acetate in 2-5 years old children with atopic dermatitis - Yazdi, Quazi Salim; Huda, Md Shamsul; Khan, Abdul Latif; Hasan, Md Sayeed; Ahmad, Mushtaq; Rosie, Tawhida Nawazesh (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Atopic dermatitis is a recurrent inflammatory skin disease with intense pruritus as its hallmark symptom. It often follows a chronic, relapsing course. Objectives: This comparative study was done with an aim to find out the efficacy of Tacrolimus and Hydrocortisone acetate in 2-5 year old children with Atopic dermatitis. Methods: This clinical trial was carried out on two equal groups of 60 patients. Group A was treated with topical tacrolimus ointment (0.03%) and group B with hydrocortisone acetate ointment (1%). Follow up was done at week 1, 2, 4, 8 and 12 of treatment for assessment of improvement and adverse event, which was measured by overall clinical improvement in the physician's global evaluation of clinical response. Data was collected in a predesigned data collection sheet, and analysis was performed by SPSS program (Version 12). Results: Excellent, marked and moderate improvement were observed in 19 (63.3%), 9 (30.0%), and 2(6.7%) patients of tacrolimus group and 1(3.3%), 2(6.7%) and 27(90.0%) patients of hydrocortisone group respectively. Tacrolimus group had significantly better improvement than hydrocortisone group (p<0.001). Skins burning at application site were observed significantly more in tacrolimus group 8(26.7%) than in hydrocortisone group 2 (6.7%). 53 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Conclusion: The study showed tacrolimus ointment is more effective than hydrocortisone acetate in the treatment of atopic dermatitis in paediatric patients. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22924 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014